Long‐term outcome of pT1a–b, cN0 breast cancer without axillary dissection or staging: a prospective observational study of 1543 women. Issue 10 (26th April 2020) - Ingvar, C.; Ahlgren, J.; Emdin, S.; Lofgren, L.; Nordander, M.; Niméus, E.; Arnesson, L.‐G.
Abstract : Background: The implementation of screening programmes in Sweden during the mid‐1990s increased the number of small node‐negative breast cancers. In this era before staging by sentinel node biopsy, routine axillary dissection for staging of early breast cancer was questioned owing to the increased morbidity and lack of perceived benefit. The long‐term risk of axillary recurrence when axillary staging is omitted remains unclear. Methods: This prospective observational multicentre cohort study included Swedish women diagnosed with breast cancer between 1997 and 2002. The patients had clinically node‐negative, pT1a–b, grade I–II tumours. No axillary staging or dissection was performed. The primary outcome was ipsilateral axillary recurrence and survival. Results: A total of 1543 patients were included. Breast‐conserving surgery (BCS) was performed in 94·0 per cent and the rest underwent mastectomy. After surgery, 58·1 per cent of the women received adjuvant radiotherapy, 11·9 per cent adjuvant endocrine therapy and 31·5 per cent did not receive any adjuvant treatment. After a median follow‐up of 15·5 years, 6·4 per cent developed contralateral breast cancer and 16·5 per cent experienced a recurrence. The first recurrence was local in 116, regional in 47 and distant in 59 patients. The breast cancer‐specific survival rate was 93·7 per cent after 15 years. There were no differences in overall or breast cancer‐specific survival between patients who received adjuvant radiotherapy and those who did not. Only 3·0 per cent of patients had an axillary recurrence, which was isolated in only 1·0 per cent. Conclusion: Axillary surgery can safely be omitted in patients with low‐grade, T1a–b, cN0 breast cancers. This large prospective cohort with 15‐year follow‐up had a very low incidence of axillary recurrences and high breast cancer‐specific survival rate. Abstract : This observational study included 1543 patients with T1a–b low‐grade breast cancer operated without axillary dissection and followed up for at least 15 years. The axillary recurrence rate was 3·0 per cent and the breast cancer‐specific survival rate 93·7 per cent. Patients who received adjuvant radiotherapy had fewer locoregional recurrences than those not receiving radiotherapy, but there was no significant difference in overall or breast cancer‐specific survival. Omit sentinel node biopsy in this group? Abstract : Antecedentes: La puesta en marcha en Suecia, a mediados de los años 90, de los programas de cribaje aumentó el número de cánceres de mama precoces con ganglios negativos. En esa era, antes de la estadificación mediante la biopsia del ganglio centinela, se cuestionó la disección axilar rutinaria para la estadificación del cáncer de mama precoz debido a su aumento de la morbilidad y la falta de percepción de beneficio. El riesgo de recidiva axilar a largo plazo cuando no se omite la estadificación axilar sigue sin estar claro. Métodos: Estudio de cohortes prospectivo, observacional y multicéntrico de las mujeres suecas diagnosticadas de cáncer de mama entre 1997‐2002. Se incluyeron las pacientes con ganglios clínicamente no detectables, pT1a‐b, grados I‐II y no se realizó disección/estadificación axilar en ninguna de ellas. El resultado principal fue la recidiva axilar ipsilateral y la supervivencia. Resultados: Se incluyeron 1.543 pacientes. Se realizó cirugía conservadora de la mama ( breast conserving surgery, BCS) en el 94% de las mujeres y en las restantes se practicó una mastectomía. Tras la BCS, el 58% de las mujeres recibió radioterapia adyuvante, el 12% tratamiento endocrino adyuvante y el 32% no recibió ningún tratamiento adyuvante. Tras una mediana de seguimiento de 15, 5 años, el 6% desarrolló un cáncer de mama contralateral y un 14% una recidiva. La primera recidiva fue local en 116 pacientes, regional en 47 y a distancia en 59. La supervivencia específica para el cáncer de mama a los 15 años fue del 94%. No hubo diferencias en la supervivencia general o específica por cáncer de mama entre las pacientes que recibieron radioterapia adyuvante y las que no. Solo el 3% de las pacientes presentó una recidiva axilar, de las cuales tan solo el 1% padecieron exclusivamente una recidiva axilar. Conclusión: La cirugía axilar se puede omitir con seguridad en los cánceres de mama de bajo grado, T1a‐b, cN0. Esta gran cohorte prospectiva con un seguimiento de 15 años muestra que la incidencia de recidivas axilares es muy baja y la supervivencia específica por cáncer de mama muy alta.